(untitled) (Perner’s Contacts, 2021)
The article proposes a concept of a catalogue systematizing the so-called non-driving activities of truck drivers, which they could perform with the development of automation of road vehicles. In the near future, this is mainly a partially automated operation without full automation, in which it is still necessary for the driver to take control of the vehicle if necessary. Nevertheless, the trend of automation of truck operation will bring a number of opportunities to effectively use the working time of future drivers, which is currently devoted primarily to driving. The authors present step-by-step steps towards the genesis, analysis and classification of activities that drivers will be able to perform in a vehicle when they are not actively driving. Context induction methods in the form of mind maps, comparisons, classification and functional analysis and classification were used. The catalogue focuses on two levels of automation of L3 and L4 vehicles according to the SAE standard. The systematic structure of the catalogue is based on numerical codes categorizing activities on at least four levels. The article presents groups of activities: mental creative activity; communication; administration, physical activity; education; fun and relaxation. An example of a part of a completed catalogue is also included. Finally, other directions of development of the proposed catalogue concept are recommended. In the future, the catalogue will be used by managers of transport companies to create the composition of the work of their employees. Other users will be, for example, central state administration bodies, educational institutions and other professional organizations in transport.